Effect of Combined Treatment of Acupuncture and Tuina Massage on Rehabilitation of Joint Function after Ankle Fracture Surgery - LONG Teng; XU Ming; ZUO Yuxuan; ZHOU Qian; LU Qiyang; LI Naping (康复学报)
ObjectiveTo observe the effect of acupuncture and tuina combination therapy on postoperative joint function rehabilitation in patients with ankle fractures.MethodsA total of 98 patients with ankle fractures admitted to the Department of Limb and Joint of the First Hospital of Hunan University of Chinese Medicine from June 2021 to June 2023 were selected. They were divided into two groups according to the envelope method, including 48 cases in the control group and 50 cases in the observation group. The control group was given rehabilitation function training from the day after surgery; the observation group was given combined acupuncture and massage treatment in addition to rehabilitation function training from the second to the seventh day after surgery. The differences in ankle Visual Analogue Scale (VAS) scores between two groups were evaluated on the first day after surgery, the first week after surgery, and the fourth week after surgery. The ankle swelling values and toe nailfold microcirculation indicators of the two groups were measured on the first day after surgery, the fourth week after surgery, and the twenty-fourth weeks after surgery. The differences in ankle joint range of motion, American Orthopaedic Foot & Ankle Society (AOFAS) scores, and activities of daily living (ADL) scores between two groups were compared on the first day after surgery, the fourth week after surgery, and the twenty-fourth weeks after surgery.ResultsCompared with the first day after surgery, the ankle pain scores and swelling values of both groups decreased at the first and fourth weeks after surgery (P<0.05). There was no statistically significant difference in the ankle pain score and swelling value between two groups on the first day after surgery (P>0.05), but the ankle pain scores and swelling values of the observation group decreased at the first week and fourth week after surgery compared with the control group (P<0.05). Compared with the first day after surgery, the number of vascular arches, the diameter of the arch top and the length of the input branches increased in both groups at the first and fourth weeks after surgery (P<0.05). There was no statistically significant difference in the microcirculation indicators of the toe nailfold between the observation group and the control group on the first day after surgery (P>0.05), but the number of vascular arches, the diameter of the arch top and the length of the input branches increased at the first and fourth weeks after surgery compared with the control group (P<0.05). Compared with the first day after surgery, the range of motion of dorsiflexion, plantar flexion, eversion and inversion of both groups increased at the fourth and twenty-fourth weeks after surgery (P<0.05). Compared with the control group, there was no statistically significant difference in the range of motion of the ankle joint in the observation group on the first day after surgery (P>0.05), but the range of motion of dorsiflexion, plantar flexion, eversion and inversion of the observation group increased significantly at the first and fourth weeks after surgery (P<0.05). Compared with the first day after surgery, the AOFAS score and ADL score of both groups increased at the fourth and twenty-fourth weeks after surgery (P<0.05). Compared with the control group, there was no statistically significant difference in the AOFAS score and ADL score between the observation group and the control group on the first day after surgery (P>0.05), but the AOFAS score and ADL score of the observation group increased at the fourth and twenty-fourth weeks after surgery (P<0.05). During the treatment period, no adverse events such as subcutaneous ecchymosis or infection occurred.ConclusionCombined acupuncture and tuina therapy can promote the recovery of ankle joint function and improve the activities of daily living in patients after ankle fracture surgery.